An analysis of Hofstede’s cultural dimensions in communication journals (Herald of Journalism, 2026)
Building off previous research exploring how communication journals and researchers have used Hall’s constructs, the current study uses Natural Language Processing (NLP) to examine how communi-cation journals have framed Hofstede’s cultural dimensions. The significance of this study is underscored by the imperative for an empirical examination of the accumulated “archaeology of knowledge” within the discipline, particularly amidst the contemporary crisis of reproducibility in scientific research.The analysis revealed that 438 articles referenced Hofstede 4,779 times. The Journal of Intercultural Communication Research published the most articles, highlighting its significance in intercultural and cross-cultural communication scholarship. Articles focused primarily on the concept of individualism vs. collectivism, with five other frames emerging: 1) the impact of cultural values in international interac-tions, 2) cross-country comparisons, 3) the interplay between uncertainty avoidance, masculinity, and power distance, 4) the influence of culture on organizations, and 5) understanding high-power distance cultures. There were also longitudinal trends and spikes in the frames over time.Methodologically, the study utilized BERTopic modeling for thematic extraction and the NLTK li-brary for the rigorous preprocessing of texts from 25 core communication journals spanning 1993 to 2024. Drawing upon Entman’s framing theory, the research elucidates how editors and authors operate as “gatekeepers” of disciplinary discourse. The longitudinal trends and cyclical spikes identified in spe-cific frames demonstrate the evolution of cross-cultural theory in response to global shifts. These findings expand the methodological repertoire for meta-synthetic research in the social sciences and provide a robust foundation for future scholarly inquiry into the trajectory of communication theory.
Keywords: Natural Language Processing, BERT analysis, Hofstede, cross-cultural communication, journal publishing.